Systematic review on genomic insights into antimicrobial resistance in ESKAPE pathogens - Husna F. Ibrahim; Nasiru Abdullahi; Ibrahim Yusuf; Bashir I. Waziri; Ahmad Abdulhadi; Khadija Muhammad; Maryam M. Ibrahim; Aisha A. Abdullahi; Muhammad A. Abbas; Hamisu M. Salihu (African Journal of Laboratory Medicine, 2026)
Background: Antimicrobial resistance (AMR) is a major global public health threat. ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp.) pose a major threat owing to resistance to last-line antibiotics. Genomic surveillance is crucial to understanding global and regional antimicrobial resistance genes (ARGs) in AMR transmission. Aim: This systematic review synthesised global genomic evidence to identify global and region-specific ARGs distribution among ESKAPE pathogens. Methods: Following PRISMA guidelines, studies published January 2019 to December 2024 were identified from PubMed, Google Scholar, and Web of Science. Eligible studies reported genomic characteristics and resistance patterns of one or more ESKAPE pathogens from any source. Results: Seventy-seven studies were included, with most originating from Asia, followed by Europe and Africa. Clinical isolates predominated K. pneumoniae was the most frequently investigated pathogen, followed by S. aureus, P. aeruginosa, and A. baumannii. The most reported resistance genes were blaCTX-M, blaNDM, and blaSHV. Distinct regional patterns of antimicrobial resistance gene (ARG) distribution were observed, with tetracycline and quinolone resistance genes prevailing in Africa and South America, and blaOXA variants dominating in Asia and Europe. Region-specific ARG patterns were identified through descriptive synthesis and comparative analysis of study-reported frequencies. Conclusion: This review provides a synthesised global map of ARG distribution in ESKAPE pathogens, highlighting surveillance gaps in underrepresented regions and non-clinical settings. Addressing these gaps will support targeted genomic surveillance and stewardship programmes. What this study adds: This study contributes to the body of knowledge by mapping global and regional antimicrobial resistance gene patterns in ESKAPE pathogens, identifying key surveillance gaps and informing targeted AMR monitoring and stewardship strategies.